Determinant Analysis of Corn Production in Lengkiti District, Ogan Komering Ulu Regency - Anggriyani, Wiwit; Sari, Yunita; Oktarina, Yetty (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
The purpose of this research was to find out the factors that affect corn production and the economic efficiency of corn farming in Lengkiti District, Ogan Komering Ulu Regency. This research was located in Bandar Jaya Village, Fajar Jaya, Karang Endah, Pagar Dewa and Umpam Lengkiti District, Ogan Komering Ulu Regency. Respondent farmers are corn farmers in Bandar Jaya, Fajar Jaya, Karang Endah, Pagar Dewa, and Umpam villages selected by a simple random sampling method of as many as 135 people. The factors of production are analyzed by the Cobb-Douglas equation method which is processed into multiple linear regressions with SPSS applications where the dependent variables are y as production and the variables and free or independent variables are X1 land area, X2 Seedlings, X3 Fertilizers, and X4 Labor for the efficiency of corn Farming Economy are analyzed with technical efficiency and price efficiency data processed with frontier applications. The results showed that the factors of seed production, fertilizer, and labor had a simultaneous effect on corn production, while partially variables of land area and fertilizer production facilities had a significant effect on corn production in Bandar Jaya, Fajar Jaya, Karang Endah, Pagar Dewa, and Umpam villages. The results of the technical efficiency analysis showed that the efficient means of 0.10 is said to be inefficient in the use of factors because it is much close to 1. The price efficiency of corn farming, which is 7.438 shows that corn farming in Bandar Jaya, Fajar Jaya, Karang Endah, Pagar Dewa, and Umpam villages is not priced efficient. As for the economic efficiency of corn farming in Bandar Jaya, Fajar Jaya, Pagar Dewa, Karang Endah, and Umpam villages, which amounted to 0.7438 this shows that corn farming is not economically efficient.